PERENCANAAN PENJUALAN UNTUK MENCAPAI LABA MINIMUM CV. JAWA INDAH DENGAN MENGGUNAKAN BREAK EVENT POINT - Mewoh, Ignatiar Keyko Diana; Saerang, David P.E.; Tirajoh, Victorina (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Rise in soybean prices in 2013 dwarfed the industry for producing tofu, tempeh, consequently emerged a call for strike is due to production losses due to the impact of rising soybean prices. This is very regrettable because remember eating tofu and tempeh are typical of Indonesia. The purpose of this study was to determine the amount of sales that must be maintained, at least have achieved sales companies as well as predict the effect of changes in critical elements of break-even point. This type of research is descriptive quantitative case study using the CV. Java Indah village of Tumpaan I, South Minahasa regency and the variables studied are not subject to an act of manipulation. The results showed that the sales should be maintained by the company is selling the product out with a minimum of Rp. 608.766.084 in the year 2013 than it changes the defining element of planning the break-even effect on the profit when selling price rise resulted in the break-even point and profit climbed down.